2019
DOI: 10.1111/jphd.12329
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyls/polyfluoroalkyl substances and dental caries experience in children, ages 3–11 years, National Health and Nutrition Examination Survey, 2013–2014

Abstract: Objective: The objective of this research is to determine the association of seven perfluoroalkyl and polyfluoroalkyl substances versus dental caries experience in US children, ages 3-11 years. Methods: A cross-sectional study design was used in the analysis of National Health and Nutrition Examination Survey 2013-2014 serological data of perfluoroalkyl and polyfluoroalkyl substances. The seven perfluoroalkyl and polyfluoroalkyl substances were: 2-(N-methyl-perfluorooctane sulfonamide) acetic acid; perfluorode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Further, little is known about the direct association between unsafe water, unsafe sanitation, and ECC despite caries being referred to as a hygiene-related disease (17). One study indicated that perfluorodecanoic acid, an industrial surfactant found in drinking water systems, may disrupt the healthy development of enamel and increase its susceptibility to caries, including ECC (18). Another study showed a lack of association between ECC and water and sanitation as measures of poverty (19).…”
mentioning
confidence: 99%
“…Further, little is known about the direct association between unsafe water, unsafe sanitation, and ECC despite caries being referred to as a hygiene-related disease (17). One study indicated that perfluorodecanoic acid, an industrial surfactant found in drinking water systems, may disrupt the healthy development of enamel and increase its susceptibility to caries, including ECC (18). Another study showed a lack of association between ECC and water and sanitation as measures of poverty (19).…”
mentioning
confidence: 99%
“…22 The ICDAS-II scores for the dental caries diagnosis included the following: 0-sound tooth; 1-first visual change in enamel; 2-distinct visual change in enamel; 3-localized enamel breakdown; 4-underlying dark shadow from dentin; 5-distinct cavity with visible dentin; and 6-extensive distinct cavity with visible dentin. 22 The prevalence of ECC was measured with ICDAS-II scores using the threshold of ICDAS-1 and any caries lesion present (d [1][2][3][4][5][6] ). The severity of ECC was determined using two other thresholds: ICDAS-2, including advanced non-cavitated and cavitated lesions (d [2][3][4][5][6] ); and ICDAS-3, including advanced lesions (d [3][4][5][6] ).…”
Section: Early Childhood Caries Experiencementioning
confidence: 99%
“…22 The prevalence of ECC was measured with ICDAS-II scores using the threshold of ICDAS-1 and any caries lesion present (d [1][2][3][4][5][6] ). The severity of ECC was determined using two other thresholds: ICDAS-2, including advanced non-cavitated and cavitated lesions (d [2][3][4][5][6] ); and ICDAS-3, including advanced lesions (d [3][4][5][6] ).…”
Section: Early Childhood Caries Experiencementioning
confidence: 99%
See 2 more Smart Citations